(untitled) (Journal of Philosophy Culture and Political Science, 2020)
The article discusses the problematics of interdisciplinary study of human rights and the possibility of development of a coherent theoretical basis thereof that would contribute immensely into the human rights field both academically and practically. The question the author raises is whether there would be a possibility for human rights scholars to go beyond legal positivism and to overcome postmodernist methodological cul-de-sac or whether there may be such an analytical framework that would provide the tools necessary to supplement the contemporary human rights studies conducted within social sciences and humanities – which are almost inclusively descriptive – with a number of explanatory models. The article presents the comparative and critical analysis of the theoretical findings in the literature on human rights by the numerous scholars in history, philosophy, international relations, anthropology and ethnology, as well as natural science in order to establish the premises upon which it could be possible conduct effective interdisciplinary research on human rights which would include where analysis units are Individual, groups of individuals, communities, nations and supranational structures respectively. Key words: sociology, human rights, paradigmatic impasse, interdisciplinary research.